The Influence of Personal Selling, Direct Selling, and Advertising on ASN Customers’ Decisions to Choose Multi-Purpose Motorcycle Financing Products at Bank Sumut Syariah KCP Rantau Prapat - Melani Adila Putri; Muhammad Syahbudi; Nurwani (Universitas KH. Abdul Chalim Mojokerto, 2025)
The purpose of this study is to examine how advertising, direct sales, and personal sales influence the decisions of civil servants (ASN) in choosing multipurpose financing (PMG) options for motorcycles at Bank Sumut Syariah KCP Rantau Prapat. The methodology used is quantitative survey research using questionnaires as a research tool. The survey will be given to customers of Bank Sumut Syariah KCP Rantauprapats multifunctional motorcycle loan products. The sampling method used was incidental sampling and the following slovin formula, and data analysis was performed using SPSS version 25, which included multiple linear regression analysis. The study findings show that although direct sales and advertising have a significant positive impact on consumer decisions, personal sales have a positive but negligible impact. Together, these three variables contribute 64.1% to ASN customer decisions, while other factors outside the scope of this study influence 35.9%. The implications of this study highlight the importance of Islamic banks maximizing face-to-face promotion and innovative advertising to increase ASN interest and encourage more participatory assessment of personal marketing tactics. To obtain a more comprehensive picture, further research is recommended to examine additional elements, including service quality, trust, and Islamic financial knowledge.